POLITIK IDENTITAS AGAMA LOKAL (Studi Kasus Aliran Kebatinan) - Hakiki, Kiki Muhamad (Analisis: Jurnal Studi Keislaman, 2011)
Even  though  experiencing  much  discrimination  in this country,  the existence of  local religion such as mysticism stream steadily grows and even still attracts many followers. Truth claim that is frequently voiced by formal religions such as Islam, Catholic, Christian, Buddha, Hindu and Confucius is not frightening to adherents of  local religion, even less converting to another belief. Interestingly, the adherents’ belief  of formal religion whether aware or not often has mixed with the belief  of local religion